Disordered wax platelets on Tradescantia pallida leaves create golden shine. (5th August 2020) - van de Kerkhof, Gea T.; Schertel, Lukas; Poon, Rebecca Nokjan; Jacucci, Gianni; Glover, Beverley J.; Vignolini, Silvia
Abstract : Disordered arrangement of wax platelets on Tradescantia leaves increase long wavelength reflectance, contrary to the commonly observed UV-protection mechanism. Abstract : Plants have various strategies to protect themselves from harmful light. An example of such a protective mechanism is the growth of epicuticular nanostructures, such as a layer of hair or wax crystals. Most nanostructures are optimised to screen UV radiation, as UV light is particularly damaging for cellular tissue. We find that, contrary to the commonly found UV reflectance, the epicuticular wax crystals on Tradescantia leaves reflect strongly in the higher visible wavelength regime. Thus, they give the leaves a golden shine. We characterize the optical appearance of Tradescantia pallida 'purpurea' leaves by angularly resolved spectroscopy and compare the results to finite difference time domain simulations. We find that it is the disordered assembly of the wax platelets that is the crucial parameter to obtain the observed reflected intensity increase for higher wavelengths.